Pengaruh Kinerja Keuangan terhadap Nilai Perusahaan Peran CSR sebagai Pemoderasi di PT. Aneka Tambang, PT. Adaro Minerals Indonesia, dan PT. United Tractor - ., Satryani; Arifin, Syamsul; Anisa, Nur Aini (CV. ITTC INDONESIA, 2025)
Financial performance is an essential indicator in assessing a company’s success, as it reflects the ability of the company to maintain business continuity and attract investors. The research aims to describe the analysis of the influence of financial reports on company value at PT. Aneka Tambang, PT. Adaro Minerals Industri, and PT. United Tractor in 2009-2023. The data studied were annual reports at PT. Aneka Tambang, PT. Adaro Minerals Industri, and PT. United Tractor in 2009-2023. The data collection technique used was documentation. The data analysis technique used was quantitative descriptive analysis. The results of this study are based on the profitability ratio using the Return Off Asset formula, the liquidity ratio using the Current Ratio formula, the solvency ratio using the Debt to Accet formula, the company value ratio using the Tobin'Q formula and the corporate social responsibility ratio using the CSRDIj = ⅀ Xij / Nj formula. The benefits of the profitability ratio, liquidity ratio, solvency ratio, company value ratio and corporate social responsibility ratio are to assess the company's financial performance whether it is in good condition or otherwise.